The Conspiracy of Us - Book 1 - Hall, Maggie 1982- (New York, NY : G.P. Putnam's Sons, an imprint of Penguin Group (USA), 2015)
When sixteen-year-old Avery West learns her family is part of a powerful and dangerous secret society, and that her own life is in danger, she must follow a trail of clues across Europe.
Keywords: Secrecy -- Juvenile fiction; Secret societies -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Families -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Secrets -- Fiction; Secret societies -- Fiction; Identity -- Fiction; Families -- Fiction; Voyages and travels -- Fiction; Mystery and detective stories; Europe -- Fiction; Europe -- Fiction